1962
DOI: 10.1083/jcb.15.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Biochemical Study of Secretory Granules From Rat Pituitary Glands

Abstract: A B S T R A C TSecretory granules from anterior pituitary glands of young adult male castrate rats were isolated by differential centrifugation, microfiltration, and discontinuous density gradient centrifugation. The granules wcre obtained as pellets, sectioned, and studicd with the electron microscope. A major part of the gonadotropin and a substantial amount of the TSH were associated with the isolated granules. Negligiblc amounts of growth hormone and prolactin were present as contaminants. Succinic dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1963
1963
1980
1980

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…There are strong arguments for the enzyme being a trypsin-like enzyme and probably it is an alkaline proteinase (9). In view of this, it is interesting that alkaline proteinase has been demonstrated in association with isolated pituitary granules (46).…”
Section: Discussionmentioning
confidence: 98%
“…There are strong arguments for the enzyme being a trypsin-like enzyme and probably it is an alkaline proteinase (9). In view of this, it is interesting that alkaline proteinase has been demonstrated in association with isolated pituitary granules (46).…”
Section: Discussionmentioning
confidence: 98%
“…16) (CARDELL and KNIGHTON, 1966;FUKUMITSU, 1964;GUSEK, 1962;LUSE, 1962;SCHELIN, 1962;WECHSLER and HOSSMANN, 1965 RINEHART, 1954 a, b, 1955;HYMER, MCSHAN and CHRISTIANSEN, 1961;LUNDIN and SCHELIN, 1962;rat, BARNSE, 1962;SANG, 1962;UCHIDA, 1967;YAMADA and SANO, 1960;mouse, SALAZAR, 1963;YOUNG, FOSTER andCAMERON, 1965, 1966;rabbit, CARDELL, 1964 a, b;salamander, OZTAN, 1966;fish MCSHAN and RIS, 1960;HYMER and MCSHAN, 1963;MCSHAN, 1964;PERDUE and MCSHAN, 1962).…”
Section: Fig 1 Low Power Electron Micrographmentioning
confidence: 99%
“…'Alkaline proteinase' activity has been demonstrated in purified anterior-pituitary-lobe granule fractions (Perdue & McShan, 1962;Tesar et al 1969) and in other endocrine tissues, the adrenal gland and the thyroid gland (Todd & Trikojus, 1960). It seemed possible that alkaline ribonuclease activity would be localized in the granule fraction from homogenates of posterior pituitary lobes, especially as Philippu & Schumann (1964) have shown that adrenal-medullary granules contain ribonuclease activity.…”
Section: Lmentioning
confidence: 99%
“…The demonstration of 'alkaline protease' activity in purified anterior-pituitarylobe granule fractions (Perdue & McShan, 1962;Tesar, Koenig & Hughes, 1969) led us to wonder whether alkaline ribonuclease is localized in the granule fraction of homogenates of posterior pituitary lobes.…”
Section: Lmentioning
confidence: 99%
See 1 more Smart Citation